PROBABILISTIC SEISMIC HAZARD ANALYSIS IN NORTHERN SUMATERA - Permana, Muhammad Aji (Jurnal Neutrino, 2018)
Northern Sumatera is one of Indonesian region that prone to earthquake. On the other hand, this region has a high level of vulnerability, because of large number of population and high economic growth rate. Thus seismic hazard analysis is needed to analyze earthquake hazard in this region. Probabilistic seismic hazard analysis being carried for count uncertainty factor, ie size, location, and frequency of the earthquake. This method consists of source identification, source characterization, attenuation function selection, and seismic hazard counting. After being calculated, the Northern Sumatera region has hazard value between 0.05 – 1.3 g. The region that has maximum hazard value is the group of islands in western Sumatera, and the minimum one is in the eastern coastline of Sumatera. Banda Aceh and Padang Sidempuan City have a medium level of earthquake hazard, with the most dominant source from Sumatera shear fault. Meulaboh and Gunung Sitoli City have a medium level of earthquake hazard, with the most dominant source from the subduction zone. Medan and Lhoksuemawe City have a low level of earthquake hazard, with the most dominant source from the deep and shallow background.